Estudo dos efeitos psicológicos decorrentes de eventos traumáticos em jovens: o impacto da guerra em Angola - Nacandumbo, Maria Manuela (2017)
The present research aimed to understand the psychological effects on young people, resulting from traumatic events of the war in Angola. The following questions were researched: what were the traumatic experiences of war that the youth experienced, and how the war events affected and impacted their lives today. With respect to the research method, a qualitative study was done. For the survey data collection, two instruments were used: a self-completed questionnaire and drawings about the experience of war. The participants were high school students of the Santa Maria Goretti Missionary School in N'dalatando, capital of the Province of Kwanza Norte, Angola. 99 students, of both sexes, agenda between 16 and 26, participated in the study. The data were entered and analyzed in SPHINX software, aided by Excel and Word Cloud. The data were analyzed in the light of the specialized literature and organized into categories. The research was submitted and authorized by the Research and Ethics Committee, under the number of Opinion 2,071,586 and CAAE: 67127917.0.0000.5482. The results revealed that the participants, in their majority, the children, went through experiences of personal suffering, of their families, friends and even strangers. They saw people killed, mutilated, mistreated, psychologically and physically tortured, attacked and destroyed. There have also been several deprivations, such as hunger, thirst, lack of shelter and basic health care. They have pointed to various consequences of psychological and physical trauma, underdevelopment, in all dimensions of life, and marked moments of difficult overcoming and forgetfulness that impact their lives today. They expressed feelings of loss, irritability, sadness, fear, guilt, revolt, indifference, resentment, grief, disgust, abandonment, loneliness, repentance, hurt, hatred, anguish and pain